Design and fabrication of Windchill for low cost vegetable preservation (Progressive Agriculture, 2019)
In Bangladesh, every year a huge amount of vegetables are being lost after harvesting from the field due to inadequate storage facilities at farmers’ level. Considering this a low cost storage chamber, windchill was designed and fabricated that consumes low power to operate by a 12V duct fan. The average temperature inside the chamber at no load condition was found 24.7◦C with a relative humidity of 77.2% while the outside temperature and relative humidity were 28.9◦C and 54%, respectively. Performance of the chamber was tested keeping vegetables inside the chamber for four and five days during pre-test and bulk load test, respectively. During bulk load test the temperature and relative humidity inside the chamber were 24.7◦C and 77.1%, respectively while outside the chamber, these were 28.8◦C and 52.8%, respectively. After four days weight loss percentage inside the chamber at pre-test condition were 1.76% (tomato), 3.53% (brinjal), 5.2% (greenchili) and 18.16% (red amaranth) while weight loss outside the chamber were 4.18% (tomato), 9.52% (brinjal), 14.44% (greenchili) and 49.44% (red amaranth). Weight loss percentage at bulk load condition inside the chamber was 1.46% while outside the chamber was 15.15% at 5th day. Physical appearance of vegetables kept inside the chamber was also much better than those kept outside the chamber. The panel test result for evaluating physical appearance was found satisfactory based on their acceptance level after preservation. The initial construction cost of the full unit was Tk. 6010 which was found cost effective for farmers to store their vegetables for several days after harvesting.Progressive Agriculture 30 (2): 209-218, 2019